Every Story Tells a Story That Has Already Been Told: Intertextuality and Intermediality in Philip Pullman's Spring-Heeled Jack and in Kevin Brooks' iBoy - Michael C. Prusse (CLELEjournal, 2014)
Training English teachers involves acquainting them with suitable texts for their future classrooms. Ideally such texts touch upon matters that children and young adults respond to and such literature also offers learning opportunities both for the pre-service teachers and their students. It can be argued that such learning opportunities can be found when analysing superheroes, when considering the impact of the new media on young people or when focusing on the blending of different genres and texts. The two novels selected for this purpose are Philip Pullman's Spring-Heeled Jack (1989) and Kevin Brooks' iBoy (2010). The former is a hybrid of a traditional and a graphic novel and resorts to intertextual allusions, for instance by means of quotes at the beginning of each chapter. The latter text also resorts to quotations - but from different sources, namely almost exclusively from the worldwide web. While iBoy may at first sight look rather conventional as a novel, it nevertheless reveals its provenance from the digital age in the numbering of the chapters in the binary system. Young readers (and their teachers) may thus discover the pleasures of literary reading when following Pullman's superhero (taken from a Victorian penny-dreadful) across London. Brooks' hybrid protagonist, by contrast, a first-person narrator, allows readers to gain insights into the problematic side of his role and his powers. Ultimately these rather conventional novels succeed in capturing their readers' attention and somewhat contradict critics who predict the arrival of a more hypertextual approach to reading because of the impact of the new media.